Understanding Financial Resiliency: A Qualitative Inquiry into the Experiences and Strategies of The Employees in an Engineering and Consultancy Firm - Siman, Bennegreg P.; Orencia, Abrian Joy B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of this qualitative case study was to conduct an in-depth analysis of the potential of Forex Trading and investing in developing financial resiliency among the employees of an Engineering and Consultancy Firm in the Philippines. This is a qualitative single case study of 10 employees of the company that were interviewed regarding the potential of investing in forex trading as a means to attain financial resiliency. Qualitative data for this study were gathered through one-session, semi-structured interviews, focus group discussions, documents, journaling, and observations. Thematic analysis following Braun and Clarke’s method for analysing qualitative data was used in understanding the qualitative data. Results have shown that participants have identified several challenges that seem to slow them down in earning money for them to obtain their aspiration of becoming financially resilient. It was also shown that participants thought that venturing in new business, stock market and forex investments, and sideline jobs were the most frequent responses recorded that may serve as solutions to the challenges. It is important to note that most of the participants were affirmative upon being asked if they would try foreign exchange investments as a potential means of achieving financial resiliency. Among others, the most significant manner of addressing financial challenges lamented by the participants was having a well-conditioned mind so that a well-planned long-term goal will be established. It is recommended to explore more related literature that tackles financial education in the Philippines and note the statistical number of those who are financially literate as this could be a contributing factor why the participants of this study lack concrete saving plans. Moreover, further exploration on the trend of foreign exchange investment is also suggested including the use of digital platforms for information dissemination regarding finance.